Desalination technologies: a critical review - Baradey, Yehya; Hawlader, Mohammad Nurul Alam; Hrairi, Meftah; Ismail, Ahmad Faris (MIJP Publication, 2018)
The current world population is expected to increase to about 9 billion in the next fifty years, which will increase the intake of fresh water significantly. Purified water for drinking purposes has become problem especially in arid regions, and is considered, nowadays, one the most significant international health issue. Billions of Dollars are currently spent worldwide on different desalination technologies to produce fresh water from Brackish and Seawater in order to meet the world’s population demand for drinking water. Demands for reducing the cost of the desalination processes by reducing/ eliminating the input energy have recently become a trend and significant topic for researches. Therefore, the need for decreasing or if possible eliminating the dependency of desalination technologies on fossil fuel and oil and make them environmentally friendly through integration with renewable energy sources has become inevitable. In this paper, a critical review of different aspects relevant to desalination technologies has been presented. The review includes demonstration and comparative study of the most popular desalination technologies currently in use and the focus is on Membrane desalination (MD). It also includes the advantages and feasibility of integration the desalination technologies with solar energy or waste heat sources. Recent developments in cost of Seawater and Brackish water desalination, types of membrane desalination, types of membrane, and fouling of membrane have been considered.